What Should We Consider Before Making Compost? - ฤทธิ์เดช, นันทวัน (KKU Science Journal, 2013)
Agricultural waste, plants trimming waste, animal manure and household waste are wastes that can be converted into a valuable material. It is beneficial to the growth of crops and maintenance of soil fertility. Use of the chemical fertilizer in agriculture for a long time which led to the soil degradation and imbalance of organisms in the soil was also occurred. Compost production is a process that turns waste into an organic matter which calls humus. To get stable, homogeneous, useful humus product and the fermentation process occurs rapidly. Considerations and awareness are needed to know before making compost.